Exploring water in oil emulsions simultaneously stabilized by solid hydrophobic silica nanospheres and hydrophilic soft PNIPAM microgel. Issue 36 (19th August 2021) - Stock, Sebastian; Jakob, Franziska; Röhl, Susanne; Gräff, Kevin; Kühnhammer, Matthias; Hondow, Nicole; Micklethwaite, Stuart; Kraume, Matthias; von Klitzing, Regine
Abstract : Using well-defined stabilizers allows generalizable predictions on the emulsion structure of w/o emulsions stabilized by hydrophilic microgels and hydrophobic nanoparticles. Abstract : A general drawback of microgels is that they do not stabilize water-in-oil (w/o) emulsions of non-polar oils. Simultaneous stabilization with solid hydrophobic nanoparticles and soft hydrophilic microgels overcomes this problem. For a fundamental understanding of this synergistic effect the use of well defined particle systems is crucial. Therefore, the present study investigates the stabilization of water droplets in a highly non-polar oil phase using temperature responsive, soft and hydrophilic PNIPAM microgel particles (MGs) and solid and hydrophobic silica nanospheres (SNs) simultaneously. The SNs are about 20 times smaller than the MGs. In a multiscale approach the resulting emulsions are studied from the nanoscale particle properties over microscale droplet sizes to macroscopic observations. The synergy of the particles allows the stabilization of water-in-oil (w/o) emulsions, which was not possible with MGs alone, and offers a larger internal interface than the stabilization with SNs alone. Furthermore, the incorporation of hydrophilic MGs into a hydrophobic particle layer accelerates the emulsions sedimentation speed. Nevertheless, the droplets are still sufficiently protected against coalescence even in the sediment and can be redispersed by gentle shaking. Based on droplet size measurements and cryo-SEM studies we elaborate a model, which explains the found phenomena.